Silence, Distance and Disclosure: The Bleed between the Far-Right and Gaming - Kaufman, Imo (Gamevironments, 2023)
Through a close reading of oral history data, this paper demonstrates how far-right ideas circulate through discursive discourses that simultaneously conceal and disclose in gaming space. Henry Urbach's theory of the closet and queer disclosure will facilitate this, providing a framework in which we can observe how the far-right exists within gaming space whilst obscuring its proximity through fantastical distance and absence. Gaming spaces are understood as an ecosystem in which ideas can be naturalised, denaturalised and (re)produced, and this ecosystem represents the room in which Urbach's in-wall closet sits. The conceal/disclose dichotomy the far-right operates through will be explored by looking at modes of implicit identity and spatial policing. The representative possibilities of the closet will allow us to scrutinise how said identities and spaces are characterised as under threat through narratives of (self)victimisation. Said narratives, in turn, lean into far-right discourses that justify and activate certain emotions and world views. The unstable boundary the closet manifests by housing the mess (the far-right) allows the wider room (gaming space) to appear tidy; in other words, for the far-right to circulate in obscure and unaccounted for ways.